Do Status Symbols in Marketing Increase Product Evaluations? An Experimental Analysis of Group Differences on Product Evaluations for Scarce and Brand-Presence Products. Issue 3 (26th May 2016) - Childs, Michelle L.; Jin, Byoungho
ABSTRACT: The desire for status is a strong motivational force that encourages consumers to appraise products/brands associated with high social standing. This research investigates two social status marketing techniques (scarcity and the presence of a brand) on product evaluations and tests whether particular characteristics (i.e., according to gender, cultural orientation, and consumers' desire for unique products) explain differences. Based on an experimental study conducted in the United States, evaluations are higher for social status marketing techniques. Females evaluate brand-presence products more highly, and consumers with a high desire for unique products evaluate scarce products more highly. This study assists marketers in developing a successful strategy to target specific consumer groups.